DESIGN AND IMPLEMENTATION OF A MOBILE GAME WITH AUGMENTED REALITY (AR) ELEMENTS FOR ANDROID AND IOS PLATFORMS - MARCHENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study focuses on the design and development of a mobile game using augmented reality technology for the two leading mobile platforms Android and iOS. The relevance of the topic is due to the rapid development of mobile and AR technologies, which opens up new prospects for creating interactive gaming products that combine the real and virtual worlds. The purpose of this study is to develop and implement a cross-platform game “Treasures Around” using augmented reality technology for Android and iOS devices with the integration of the ARKit and ARCore frameworks through the Unity game engine. Therefore, this study addresses the issues of creating a game concept, designing architecture, developing UI/UX design, implementing AR mechanics, geolocation services, and testing on real devices. A comparative analysis of the Unity and Unreal Engine game engines was conducted in terms of their suitability for developing mobile AR games. The choice of Unity as the optimal engine is substantiated due to its effective cross-platform support (AR Foundation), better optimization for mobile devices, development speed, and large ecosystem. A comparison of the ARKit and ARCore frameworks was also conducted, which emphasized the feasibility of using cross-platform solutions to support both operating systems. In accordance with the research objective, the concept of the mobile AR game “Treasure Around” was developed, in which players search for virtual treasures, moving in the real world using hints and interacting with AR objects through a smartphone camera. The main elements of the user interface focused on intuitiveness and minimalism in AR are described. The basic algorithm of the gameplay is developed, including activation of the AR mode based on geolocation and interaction with the found treasures.